2022
DOI: 10.3389/fpubh.2022.1044550
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare preferences of the general Chinese population in the hierarchical medical system: A discrete choice experiment

Abstract: BackgroundChinese health insurance system faces resource distribution challenges. A patient-centric approach allows decision-makers to be keenly aware of optimized medical resource allocation.ObjectiveThis study aims to use the discrete choice model to determine the main factors affecting the healthcare preferences of the general Chinese population and their weights in the three scenarios (chronic non-communicable diseases, acute infectious diseases, and major diseases).MethodsThis study firstly identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…T A B L E 3 Comparison of classification effects regarding the choice of medical institution and using binary logistic regression and decision-tree models. medical insurance reimbursement, and familiarity with healthcare options [8][9][10]. This to some extent explains why patients preferred hospitals for medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 3 Comparison of classification effects regarding the choice of medical institution and using binary logistic regression and decision-tree models. medical insurance reimbursement, and familiarity with healthcare options [8][9][10]. This to some extent explains why patients preferred hospitals for medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents choose among sets of experimentally controlled sets of profiles and these choices are modeled via multinomial logit as a function of the experimental design variables [ 29 ]. However, the multinomial logit model which means it cannot tell the preference heterogeneities of different groups of respondents among the whole sampled population [ 43 ]. Thus this study was likely to favor a conditional logit regardless of whether preference heterogeneity was in fact present.…”
Section: Discussionmentioning
confidence: 99%
“… 43 In addition, a discrete choice experiment carried out in Fujian province involving 507 respondents found that urban residents show a high disposition for public healthcare providers, whereas rural residents were found to be indifferent in their preference for public vs. private healthcare providers. 44 Similarly, in a questionnaire administered to 1500 participants sampled from ten districts across Shenzhen, only 1.7% said they would seek care from a private medical institution if unwell, and no participants chose private medical institutions as their first choice for care. 45 There appears to be a clear preference among residents across China for care administered by public institutions.…”
Section: Key Challenges To Private Hospital Development In Chinamentioning
confidence: 99%